Diagnóstico del ecosistema de emprendimientos del sector del turismo en la costa norte de Manabí, Ecuador - Bravo Mendoza, Shirley Dayanna (2023)
The objective of this research was to diagnose the tourism sector in order to identify the elements and stakeholders of the tourism entrepreneurial ecosystem that will allow its evaluation in the northern coast in Manabí. Therefore, its methodological development was carried out in three phases; initially, a situational diagnosis of the tourism sector was made in order to know the current state of the territory and for this purpose a bibliographic review was carried out using the analytical and synthetic methods, likewise, an interview questionnaire was applied to the relevant entities, thus demonstrating that the study area has potential for the development of tourism enterprises, ergo, it was evidenced that there are several factors that influence their efficient development, within the second phase, the factors that allow the sustainability of the entrepreneurial ecosystem were identified, for this it was necessary to conduct a field observation in order to apply surveys that were directed to entrepreneurs and tourists, resulting in the identification of the elements present in the entrepreneurial ecosystem and in turn the perception of entrepreneurs and visitors regarding the territory, finally in the third phase a management model was developed that allowed the evaluation of the development of the entrepreneurial ecosystem, it is necessary to indicate that the Delphi technique (expert criteria) was used for the development and acceptance of the model, and that it was used for the evaluation of the development of the entrepreneurial ecosystem, it is necessary to indicate that the Delphi technique (expert criteria) was used for the development and acceptance of the model.